Bioaccumulation and distribution of 137 Cesium in the Humpback Grouper Fish (Cromileptes altivelis) - KETY MELINDA; HENY SUSENO; WAHYU PRIHATINI (Smujo International, 2015)
Melinda K, Suseno H, Prihatini W. 2015.Bioaccumulation and distribution of137Cesium in the Humpback Grouper Fish(Cromileptes altivelis). Nusantara Bioscience 7:180-184.Humpback grouper fish (Cromileptes altivelis) is a highly valuable exportcommodity of food products. The high demand of this species needs to be supported by the intensive coastal aquaculture. However, thecoastal aquaculture has been jeopardized by several threats, for an exampleradionuclide pollutant 137Cesium (Cs) generated fromnuclear reactor wastes. The pollutant accumulation in fish occurs because of continuing exposure to the pollutant-containing medium. This research was conducted from May to June 2015 at the Laboratory of Oceanic Radioecology,Center for Technology of RadiationSafety and Meteorology, National Nuclear Energy Agency, South Jakarta. This research observed the level of bioaccumulation anddistribution of 137Cs inC. altivelis bodies. Radionucleid 137Cs of 2 Bq/mL concentration was inducted to two groups of fish, i.e. mediumsize (average body mass of 65.8g) and small size (average body mass of 34.7g). The calculation of concentration factor valuesatsteady state (CFss) was done to determine the level of bioaccumulation 137Cs in fish body. The distribution of Cs in fish body wasanalyzed by calculating the percentage of accumulation 137Cs in a certain organ to the total accumulation in fish body. The resultsshowed that the value of CFss of medium size fish was 1.23 and CFss for small fish was 2.01. It means that small size fish accumulated 137Cs almost twice as much as larger fish. The accumulation of 137Cs in C. Altivelis was foundmost in its muscle (meat), which was63.34%. This research findings provide reason for us to be more careful in consuming humpback grouper fish coming from Cspolluted water due to the impact ofbiomagnifications of 137Cs in fish.